Assessing a portable, real‐time display handheld meter with UV‐A and UV‐B sensors for potential application in personal sun exposure studies - Preez, D. J.; Plessis, J. L.; Wright, C. Y. (Skin research and technology, 2018)
Background Observing accurate real‐time measurements of solar ultraviolet radiation (UVR) levels is important since personal excess sun exposure is associated with skin cancers. Handheld measurement devices may be helpful but their accuracy is unknown. We compare a portable, science‐grade solar UVR monitoring device against two fixed, science‐grade solar UVR instruments. Methods Instruments were (1) a fixed Solar Light 501 UV‐B biometer to measure UV‐B; (2) a fixed Kipp and Zonen radiometer used to measure UV‐A and UV‐B; and (3) Goldilux ultraviolet probes which are commercially available portable devices. Two different probes were used, one measured UV‐A and the other UV‐B radiation. The Goldilux probes were levelled and secured next to the UV‐B biometer. Between 10:00 and 14:40 UTC+2, the UV‐B biometer was set to record at 10‐minute intervals and measurements by the Goldilux probes were manually taken simultaneously. Results were compared for all data and by solar zenith angle (SZA) ranges. Results The Goldilux UV‐B probe measured UV‐B relatively well in its diurnal pattern, however, its readings were ~77% higher than those made by the UV‐B biometer. While UV‐A measurements from the Goldilux UV‐A probe and those from the radiometer were in relatively good agreement in pattern, the radiometer read ~47% higher than the Goldilux UV‐A probe. UV‐B data from Goldilux UV‐B probe had a moderately strong correlation with UV‐B biometer data for small SZAs; conversely, for UV‐A, the Goldilux UV‐A probe had a strong correlation with the UV‐A radiometer data for large SZAs. Conclusion Handheld devices may be useful to provide real‐time readings of solar UVR patterns, however, to achieve synchronicity in the magnitude of readings to those made by science‐grade fixed instruments, devices may need to be used during certain times of the day and in clear‐sky conditions which may not be practical in personal exposure studies.